2005
DOI: 10.1111/j.1460-9568.2004.03822.x
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of group II mGlu receptors blocks the enhanced drug taking induced by previous exposure to amphetamine

Abstract: Repeated exposure to amphetamine (AMPH) leads to the development of behavioural sensitization that can be demonstrated in rats as enhanced locomotor responding to and self-administration of the drug. Glutamate systems are known to participate in the induction and expression of sensitization by psychostimulants. Group II metabotropic glutamate receptors (mGluRs), because they negatively regulate both vesicular and nonvesicular glutamate release, are thus well positioned to gate its expression. Here we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 34 publications
5
54
0
2
Order By: Relevance
“…The higher LY379268 dose (3 mg/kg), when tested on its own in nicotine-naïve rats, decreased NAcc shell dopamine levels at some time-points postadministration compared with baseline dopamine levels (Figure 2a). This LY379268-induced dose-dependent decrease in basal NAcc shell dopamine levels in nicotine-naïve rats is consistent with previously published results (Greenslade and Mitchell, 2004;Hu et al, 1999;Kim et al, 2005;Xi et al, 2010a, b). Taken together, these findings reflect the fact that activation of mGlu2/3 receptors on presynaptic glutamate terminals decreases glutamate release, which in turn results in lower activation of dopamine neurons in areas such as the VTA and consequently decreases in dopamine release in terminal areas such as the NAcc.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The higher LY379268 dose (3 mg/kg), when tested on its own in nicotine-naïve rats, decreased NAcc shell dopamine levels at some time-points postadministration compared with baseline dopamine levels (Figure 2a). This LY379268-induced dose-dependent decrease in basal NAcc shell dopamine levels in nicotine-naïve rats is consistent with previously published results (Greenslade and Mitchell, 2004;Hu et al, 1999;Kim et al, 2005;Xi et al, 2010a, b). Taken together, these findings reflect the fact that activation of mGlu2/3 receptors on presynaptic glutamate terminals decreases glutamate release, which in turn results in lower activation of dopamine neurons in areas such as the VTA and consequently decreases in dopamine release in terminal areas such as the NAcc.…”
Section: Discussionsupporting
confidence: 81%
“…Because mGlu2/3 receptor activation negatively regulates glutamatergic neurotransmission (Cartmell and Schoepp, 2000), we hypothesized that LY379268 decreases the reinforcing effects of nicotine by attenuating nicotineinduced increases in NAcc shell dopamine. This hypothesis is supported by the observation that mGlu2/3 receptors are expressed in the NAcc shell (Testa et al, 1998), and these receptors regulate both basal and psychostimulantinduced NAcc dopamine neurotransmission (Greenslade and Mitchell, 2004;Hu et al, 1999;Karasawa et al, 2006;Kim et al, 2005;Manzoni et al, 1997;Uslaner et al, 2009;Xi et al, 2002aXi et al, , 2010a. Furthermore, activation of mGlu2/3 receptors attenuated the dopamine-dependent psychostimulant-induced enhancement of locomotor activity (Kim et al, 2005;Riegel et al, 2003).…”
Section: Introductionsupporting
confidence: 60%
“…Finally, the present findings on the effect of intra-NAc LY379268 injections in a rat relapse model extend those from our previous study on the effect of systemic and intra-VTA injections of the drug on context-induced reinstatement of heroin seeking (Bossert et al, 2004). It was also reported that systemic injections of LY379268 attenuate (1) discrete cue-induced reinstatement of heroin seeking , (2) discriminative cue-induced reinstatement of cocaine seeking (Baptista et al, 2004), (3) cocaine priming-induced reinstatement (Peters et al, 2004), (4) enhanced amphetamine-taking behavior by prior sensitizing exposure to the drug (Kim et al, 2005), and (5) other behavioral effects of abused drugs (Kenny and Markou, 2004). Together, these results from preclinical studies suggest that pharmacological manipulations that target group II metabotropic glutamate receptors should be considered in the treatment of drug addiction.…”
Section: Discussionmentioning
confidence: 98%
“…The physical environments that provided Contexts A and B were counterbalanced. Drugs LY379268 (0.3, 1.0, and 3.0 mg) was dissolved in 1.2 M NaOH solution (pH adjusted to 7.4) (Kim and Vezina, 2002;Kim et al, 2005). The bilateral intracranial doses of LY379268 were based on our previous report (Bossert et al, 2004).…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation